Sign Changes of Kloosterman Sums with Almost Prime Moduli. II: Corrigendum. (22nd July 2020) - Xi, Ping
Abstract: We give a corrigendum to the previous paper [ 8 ] and recover the same quantitative statement: the Kloosterman sum changes sign infinitely often as the modulus runs over squarefree numbers with at most seven prime factors.